Growth Patterns of Thai Children with Down Syndrome from Birth to 5 Years - Boontan, Naiyana; Rojnueangnit, Kitiwan (Journal of Pediatric Genetics, 2020)
Specific growth charts for children with Down syndrome (DS) have been developed in several countries, but not in Thailand. This pilot study aims to develop growth patterns for Thai children with DS, which will help clinicians to improve assessment and monitoring of the growth patterns for these children. A retrospective review of 80 children with DS who received care at Thammasat University Hospital between 2014 and 2018 was conducted. A total of 1,681 length/height and weight measurements were collected. Four sex-specific growth patterns of length/height and weight were generated with the fifth, 50th, and 95th percentile. The children with DS were lower in weight and shorter than general Thai children and children with DS in other countries. Therefore, each country should develop individual DS growth charts.
Keywords: growth pattern; Down syndrome; Thai; children